Social actors in an Intercultural Communication classroom: A discursive lens of intercultural education - Fuad Abdullah; - Lulita (Universitas Katolik Indonesia Atma Jaya, 2018)
This study focused on how teachers and students as the social actors in an Intercultural Communication (IC) classroom were represented discursively. A video recording transcript of IC classroom activities at a state University in Indonesia was selected as the data source. The data source was rigorously analysed through van Leeuwen’s Socio-semantic inventory of social actors framework (Van Leeuwen, 1996). The main findings show that social actors in IC classroom can be categorised into two main thematic representations, namely positive and negative ones. disclosed that Hamzah as the representative of classroom presenters was represented as victimised, oppressed, intimidated and minoritised actor. Hamzah’s Mathematics teacher was depicted as an intolerant, dehumanising, discriminatory and oppressing actor. Hamzah’s Social Sciences teacher was illustrated as a racial, stereotyping, dominant and provoking actor. The Intercultural Communication teacher was delineated as the actor endeavoring to encourage his students to be tolerant, critical, supportive and open-minded people. Hamzah’s classmates in IC classroom were characterised as sympathetic, supportive, friendly and reactionary actors.